SOCIAL AND ENVIRONMENTAL PROTECTION IN BILATERAL INVESTMENT TREATIES: FOREIGN INVESTORS’ PERSPECTIVE - Suleiman, M. Aji Satria (UI Scholars Hub, 2011)
The limit of host states’ right to regulate foreign investment within their jurisdiction has been the main, yet unresolved issues in international investment law. This makes it more difficult, given the global structure of investment law that consists of networks of Bilateral Investment Treaties (BITs). This article will not deal with the question of optimal structure of regulatory discretion under BITs which is still debatable among scholars. The central agenda of this article is to address the precondition for an efficient outcome to materialize within the complex web of BITs already signed among states. It is even more complex to be concluded. This issue is due to the absence of international coordinating institution, letting alone that of global supranational authority. This is different from the case of domestic regulatory takings which “simply” requires the correct information and measure from the benevolent government, that means, the existence of an efficient provision, if any, will not necessarily result in an efficient outcome. The main research question addressed in the article is: under what condition a capital exporting state could introduce higher flexibility for regulating public interest in an investment treaty negotiation? The article offer the answer on issue linkage between the level of protection under BIT, the degree of openness of access to domestic legal and regulatory making of the host state, and the foreign investor’s capabilities to deal with the trade-off. Ceteris paribus, the linkage enables a set of feasible Pareto improving deals out of BIT negotiation